Getting the bugs out : - Kiley, David (John Wiley & Sons, Inc., 2002)
The fascinating story of Volkswagen raging success and near collapse in America After a wild ride of ups and downs for almost three decades, Volkswagen has regained its stature as one of America most beloved auto makers. In Getting the Bugs Out, journalist and auto industry expert David Kiley tells the complete story of the rise, fall, and comeback of Volkswagen. Kiley traces the companys rise from Ferdinand Porsche original design for the Beetle, through the Nazi era, and up to the Beetle ascendancy during the flower-power 1960s. He explores the reasons for VWs downward spiral through the 1970s and 1980s, including the devastating management blunders that led to such failed efforts as the Rabbit, Dasher, Thing, and Scirocco, and equally catastrophic marketing initiatives, culminating in the notorious "Fahrfegnugen" series of ads. Finally, drawing upon his unique access to company insiders, Kiley tells the story of how Volkswagen achieved its phenomenal comeback beginning in the late 1990s through a combination of visionary management, cutting-edge product development, and brilliant marketing and advertising strategies. David Kiley (Anne Arbor, MI), the Detroit Bureau Chief at USA Today, is a journalist with fifteen years of experience, ten of which have been devoted to covering the auto industry. He has written extensively for Adweek and Brandweek magazines.